SEMANTIC TYPOLOGY OF SYNTACTIC SPECIFIERS IN UKRAINIAN MASS MEDIA - Аксьонова, Інна (Linguistic Bulletin (Movoznavchyi Visnyk), 2020)
In modern linguistics, a simple complicated sentence needs a comprehensive study. In particular, the question of the structures of concretization is considered in the works of M. Akhmedkhanova, L. Zakharova, A. Priyatkina, M. Olenyak, N. Fomina, T. Funtova and others. The semantic relations in the construction of concretization require a thorough study. The purpose of the article is to determine the semantic typology of syntactic specifiers in Ukrainian mass media. Methods. A descriptive method was used to characterize the semantic capabilities of the syntactic expression expressions. The peculiarities of the linguistic use of the concrete units in the texts of the mass communication were determined using the contextual-situational method, using the method of component analysis. Results. Syntactic specifiers, as N. Fomina notes, are explanatory constructions, refinement members of a sentence, substantive turns, homogeneous members of the sentence with a prepositional generalization word, and other adjacent semantic-syntactic phenomena. The article defines the features of the category of refinement and clarifies the regularities of expression of its semantics in the structure of syntactic specifiers of the Ukrainian language based on their use in mass media. The analysis of structural-semantic features of functioning of the category of refinement in the texts of journalistic style is made. Originality. The correlation of the components of the refinement category in the studied texts is revealed, regularities of the semantics of syntactic specifiers in mass communication are determined. The functioning of a syntax specifier, as well as any syntactic structure constructed by one of the types of communication, is possible only in the presence of corresponding semantic relations. Semantic refinement is only possible in a context or linguistic situation where the refinement is a more relevant word. Conclusion. According to the results of the research, the typology of syntactic specifiers was singled out, reference bases of realization of generic relationships, connections between general and individual in the structure of structure were determined. Depending on the specifics of the relations between the referents, the specific references in the mass media can be divided into complex-referential, base-referential and concrete-referential. It is proved that the concreteness of the texts in the texts of the mass media is used to transmit extra-linguistic information according to the communicative guidelines.